Distinct survival strategies in oligotrophic and eutrophic ecotype Synechococcus-bacteria co-cultures under iron limitation and warming conditions - Bowen He; Yu Wang; Min Xu; David A. Hutchins; Fei-Xue Fu; Xiaomin Xia; Ran Duan; Ta-Hui Lin; Nianzhi Jiao; Qiang Zheng (mBio, 2025)
ABSTRACT Phytoplankton-bacteria interactions underpin primary production and nutrient cycling in both oligotrophic and eutrophic aquatic environments, profoundly influencing marine biogeochemical cycles. Despite their importance, how these interactions vary under simultaneous environmental stressors such as warming and iron (Fe) limitation remains largely unexplored, especially across differing ecotypes. Here, we compared the responses of oligotrophic (strain YX04-1) and eutrophic (strain XM-24) ecotype Synechococcus-heterotrophic bacteria interactions to concurrent warming and Fe limitation, using the 16S rRNA gene amplicon sequencing alongside metagenomic and metatranscriptomic analyses. Our results revealed that community composition and gene expression in the oceanic Synechococcus sp. YX04-1 co-culture were more sensitive to warming, whereas the coastal Synechococcus sp. XM-24 co-culture responded more strongly to Fe limitation. The resilience of oligotrophic YX04-1 and its bacterial partners to iron deficiency may result from potential mutualistic triangular dynamics, involving complex carbohydrate decomposition, low-molecular-weight organic substrate transfer, and feedback of public goods. In contrast, the eutrophic XM-24 co-culture experienced intensified competition and opportunistic exploitation of organic resources by dominant mixotrophic bacteria under concurrent warming and Fe limitation conditions. These findings reveal contrasting survival strategies of oligotrophic and eutrophic Synechococcus-bacteria co-cultures, highlighting the tighter and mutually beneficial interactions in the oligotrophic co-culture that may assist oligotrophic species in adapting to changing ocean conditions.IMPORTANCEPhytoplankton-bacteria interactions serve as a crucial biological network linking primary production and nutrient cycling in marine ecosystems. In the context of global change, the upper ocean inevitably faces increased warming and iron limitation, which will shift primary producer composition toward Synechococcus and impact its nutrient exchanges with co-existing bacteria. The changes in this fundamental and widespread microbial interaction may affect the stability of nutrient cycling, yet its universal response under warming and iron limitation remains poorly understood. Our research reveals contrasting responses of oligotrophic and eutrophic Synechococcus-bacteria interactions under the same stress, driven by stronger metabolic dependencies in the oligotrophic co-culture but greater individual competitiveness in the eutrophic one. These findings emphasize the importance of cooperative heterotrophic bacteria for host survival and imply a non-uniform co-evolution of in situ microbial interactions across different marine ecosystems in the future.